Different Responses of Soil Bacterial and Fungal Communities to 3 Years of Biochar Amendment in an Alkaline Soybean Soil - Gao, Wenhui; Gao, Ke; Guo, Zonghao; Liu, Yuan; Jiang, Li; Liu, Cheng; Liu, Xiaoyu; Wang, Guangli (Frontiers in Microbiology, 2021)
Biochar as a soil amendment has been regarded as a promising way to improve soil fertility. However, the response of microbial community after biochar and biochar compound fertilizer application has not been thoroughly elucidated. This study evaluated the changes in abundance and composition of bacterial and fungal communities using quantitative real-time PCR and Illumina MiSeq sequencing. A field trial was conducted in 2017 and five treatments were set up- chemical fertilizer as control (CK), straw-returning combined with chemical fertilizer (CS), low biochar application combined with chemical fertilizer (LB), high biochar application combined with chemical fertilizer (HB) and biochar compound fertilizer (BCF). The results shown that bacterial abundance and diversity showed no significant response to biochar amendment in the bulk and rhizosphere soils. However, the abundance of soil fungi was significantly increased by biochar amendment (LB and HB). LB treatment significantly increased the fungal alpha diversity, including Chao1, ACE and Shannon indices. Furthermore, the dominant bacterial phyla found in the samples were Proteobacteria, Actinobacteria and Acidobacteria. Biochar addition increased the relative abundance of Actinobacteria in both bulk and rhizosphere soils. The dominant fungal phyla were Ascomycota, Mortierellomycota and Basidiomycota. The relative abundance of Ascomycota significantly decreased, but Mortierellomycota significantly increased in LB and HB. In addition, redundancy analysis indicated that the changes in bacterial and fungal communities are associated with soil properties such as SOC and TN, which are crucial contributors in regulating the community composition. This study is expected to provide significant theoretical and practical knowledge for the application of biochar in agricultural ecosystem.